Strengthening Cybersecurity and Data Protection Legal Framework in Indonesia: A Normative Analysis of Current Challenges and Future Directions - Ahmad Fuady; Fauzie Yusuf Hasibuan; Zulkarnaen Kotto (International Forum of Researchers and Lecturers, 2025)
Indonesia's digital transformation has accelerated dramatically, creating unprecedented opportunities alongside significant cybersecurity challenges. This article examines the current state (das sein) and normative expectations (das sollen) of Indonesia's cybersecurity and data protection legal framework through a comprehensive normative legal analysis. The study reveals critical gaps in existing legislation, particularly the Information and Electronic Transactions Law (UU ITE). It evaluates the potential impact of emerging regulatory frameworks, including the Draft Law on Personal Data Protection (RUU PDP). Using normative legal research methodology, this analysis draws from statutory regulations, policy documents, and comparative legal studies to assess Indonesia's legal preparedness for evolving cyber threats. The findings indicate that while foundational legal instruments exist, significant normative reforms are required to address sophisticated cybercrime, protect individual privacy rights, and maintain national digital security. The research concludes with actionable recommendations for legislative enhancement, institutional strengthening, and public-private collaboration to establish a robust, adaptive cybersecurity legal regime that meets international standards while addressing Indonesia's unique socio-legal context.